Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ehf2.12140
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective agent Rasagiline mesylate attenuates cardiac remodeling after experimental myocardial infarction

Abstract: AimRasagiline mesylate (N‐propargyl‐1 (R)‐aminoindan) (RG) is a selective, potent irreversible inhibitor of monoamine oxidase‐B with cardioprotective and anti‐apoptotic properties. We investigated whether it could be cardioprotective in a rat model undergoing experimental myocardial infarction (MI) by permanent ligation of the left anterior descending coronary artery.Methods and resultsRG was administered, intraperitoneally, for 28 days (2 mg/kg) starting 24 h after MI induction. Echocardiography analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…have been reported with the use of rasagiline in the post-MI rat. 56 Thyroid hormones increase alpha-MHC, SERCA-2 and decrease apoptosis; studies have shown that thyroid supplementation in the animal prevents or reverses REM. 20,57,58 Around 30 % of patients with congestive heart failure have low triiodothyronine (T3) levels, constituting the 'low T3 syndrome'.…”
Section: Novel Drugs and Therapiesmentioning
confidence: 99%
“…have been reported with the use of rasagiline in the post-MI rat. 56 Thyroid hormones increase alpha-MHC, SERCA-2 and decrease apoptosis; studies have shown that thyroid supplementation in the animal prevents or reverses REM. 20,57,58 Around 30 % of patients with congestive heart failure have low triiodothyronine (T3) levels, constituting the 'low T3 syndrome'.…”
Section: Novel Drugs and Therapiesmentioning
confidence: 99%
“…In the experimental MI model, it has been shown that rasagiline administration reduces oxidative stress, and consequently tissue MDA levels decrease. [14]Carrilo et al…”
Section: Discussionmentioning
confidence: 99%
“…[13]Varela et al demonstrated the cardioprotective effects of rasagiline in the experimental myocardial infarction model. [14]In this case, it is thought that rasagiline may have effects on peripheral diseases besides its effects on central diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Rasagiline mesylate (N-propargyl-1 (R)-aminoindan) (RG), a selective, potent irreversible inhibitor of monoamine oxidase-B, administered for 28 days (2 mg/kg) starting 24 h after myocardial infarction, preserves left ventricular geometry and function. Treatment with rasagiline prevents tissue fibrosis and attenuates cardiomyocyte apoptosis in the border zone of the infarct associated with a markedly-decreased malondialdehyde level in the border zone, indicating a reduction in tissue oxidative stress [ 178 ]. Additionally, MAO-A is an important source of oxidative stress in the heart and MAO-A-derived reactive oxygen species contribute to dilated cardiomyopathy [ 145 ].…”
Section: Monoamine Oxidases (Mao)mentioning
confidence: 99%